ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN PRODUK UMRAH UNTUK PENINGKATAN KUANTITAS CALON JEMAAH UMRAH - Zainur Ridho; Nurul Ajizah (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2024)
Business competition is getting faster and faster, demanding various companies to prepare the right strategy in maintaining the existence of their company. The travel business is not spared from the fierce competition in the business world. This research was conducted at PT. Nur Haramain Mulia. Using qualitative research methods with interviews by experts and documentation. Data analysis technique with SWOT analysis is carried out by processing interview data using the IFAS (Internal Factors Analysis Strategy) matrix and EFAS (External Factors Analysis Strategy) to determine the weight, rating, and score on each SWOT factor, which is then analyzed using the SWOT matrix to know SO, WO, ST and WT strategies. To describe the strengths and weaknesses using IFAS while the opportunities and threats use EFAS. The results of this research are strategies at PT. Nur Haramain Mulia uses a mixed marketing strategy. In an effort to increase the quantity of Umrah pilgrims, PT Nur Haramain Mulia is seeking promotions on social media, holding price discounts, collaborating with partners and opening branches in several other cities.